2006
DOI: 10.1103/physrevb.73.033106
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the photonic band gap in the presence of disorder

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 15 publications
0
20
0
3
Order By: Relevance
“…Disorder may have a dramatic influence in the transport properties of the photonic crystal. 56 On the one hand, the transmission coefficient averaged over an ensemble of random scatterers T decays exponentially with increasing length L of the disordered media, similar to Anderson's localization. 57 On the other hand disorder fights against the interference phenomena that gives rise to the existence of band gaps.…”
Section: B Entanglement Through Disordermentioning
confidence: 97%
“…Disorder may have a dramatic influence in the transport properties of the photonic crystal. 56 On the one hand, the transmission coefficient averaged over an ensemble of random scatterers T decays exponentially with increasing length L of the disordered media, similar to Anderson's localization. 57 On the other hand disorder fights against the interference phenomena that gives rise to the existence of band gaps.…”
Section: B Entanglement Through Disordermentioning
confidence: 97%
“…This question is discussed in numerous references addressing models of disorder in 1D-2D lattices [3][4][5][6][7][8] or in full 3D crystal arrangement [9][10][11][12][13][14][15][16][17][18][19]. The former models are applied to planar PhCs and photonic crystal waveguides (PCWs).…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion curve, which describes the frequency of the wave as a function of its wave vector k, provides a clear insight into all essential propagation phenomena in photonic structures. Recent theoretical studies on photonic waveguides 19,20 have demonstrated that the presence of nanometer scale disorder drastically modifies the ideal dispersion near a band edge.…”
Section: Introductionmentioning
confidence: 99%